Determinants of Profitability and DEA Efficiency Analysis of Indonesia’s Cigarette Industry - Setiawan, Chandra; Angelina, Selly (Indonesian Journal of Accounting and Governance, 2025)
Despite high smoking rates and substantial household spending on cigarettes, cigarette sales volume in Indonesia has gradually declined over recent years. Amid these challenging times in the cigarette industry, this research aims to analyze the determinants of profitability and efficiency of cigarette companies in Indonesia from 2019 to 2023. The study uses data from quarterly financial reports of four companies listed on the IDX. In panel data regression analysis, the independent variables include the current ratio (CR), assets turnover (TATO), and debt-to-equity ratio (DER), while the dependent variable is return on assets (ROA). The selected model for panel data regression is the Fixed Effect Model (FEM). The findings reveal that both CR and DER have a significant negative impact on return on assets, while TATO has a significant positive impact on ROA. All the independent variables collectively exert a significant influence on the ROA of cigarette companies. Among these variables, DER has the most significant effect on profitability. These variables explain 51.90% of the variation in ROA. Additionally, the average technical efficiency score of cigarette companies in Indonesia from 2019 to 2023 is 69.0%. Simple regression analysis further shows that the average technical efficiency score significantly and positively influences ROA, accounting for 47.68% of the variation. Overall, these variables explain 99.76% of the variation in ROA. In conclusion, cigarette companies should focus on optimizing asset use and cautiously managing debt levels to attract investors and sustain stable returns even during market fluctuations.